Comparative analysis of Cu (I)‐catalyzed alkyne‐azide cycloaddition (CuAAC) and strain‐promoted alkyne‐azide cycloaddition (SPAAC) in O‐GlcNAc proteomics. Issue 11 (1st March 2016) - Li, Shanshan; Zhu, He; Wang, Jiajia; Wang, Xiaomin; Li, Xu; Ma, Cheng; Wen, Liuqing; Yu, Bingchen; Wang, Yuehua; Li, Jing; Wang, Peng George
Abstract : O ‐linked β‐ N ‐acetylglucosamine ( O ‐GlcNAc) is emerging as an essential protein post‐translational modification in a range of organisms. It is involved in various cellular processes such as nutrient sensing, protein degradation, gene expression, and is associated with many human diseases. Despite its importance, identifying O ‐GlcNAcylated proteins is a major challenge in proteomics. Here, using peracetylated N ‐azidoacetylglucosamine (Ac4 GlcNAz) as a bioorthogonal chemical handle, we described a gel‐based mass spectrometry method for the identification of proteins with O ‐GlcNAc modification in A549 cells. In addition, we made a labeling efficiency comparison between two modes of azide‐alkyne bioorthogonal reactions in click chemistry: copper‐catalyzed azide‐alkyne cycloaddition (CuAAC) with Biotin‐Diazo‐Alkyne and stain‐promoted azide‐alkyne cycloaddition (SPAAC) with Biotin‐DIBO‐Alkyne. After conjugation with click chemistry in vitro and enrichment via streptavidin resin, proteins with O ‐GlcNAc modification were separated by SDS‐PAGE and identified with mass spectrometry. Proteomics data analysis revealed that 229 putative O ‐GlcNAc modified proteins were identified with Biotin‐Diazo‐Alkyne conjugated sample and 188 proteins with Biotin‐DIBO‐Alkyne conjugated sample, among which 114 proteins were overlapping. Interestingly, 74 proteins identified from Biotin‐Diazo‐Alkyne conjugates and 46 verified proteins from Biotin‐DIBO‐Alkyne conjugates could be found in the O ‐GlcNAc modified proteins database dbOGAP (http://cbsb.lombardi.georgetown.edu/hulab/OGAP.html ). These results suggested that CuAAC with Biotin‐Diazo‐Alkyne represented a more powerful method in proteomics with higher protein identification and better accuracy compared to SPAAC. The proteomics credibility was also confirmed by the molecular function and cell component gene ontology (GO). Together, the method we reported here combining metabolic labeling, click chemistry, affinity‐based enrichment, SDS‐PAGE separation, and mass spectrometry, would be adaptable for other post‐translationally modified proteins in proteomics.